Cuba refletida nas telas: uma análise narrativa das obras da codireção Alea-Tabío - Marina de Morais Faria Novais (2019)
This research aims to understand how the films Fresa y Chocolate (1993) and Guantanamera (1995), both co-directed by the duo Tomás Gutiérrez Alea and Juan Carlos Tabío, build their narratives as a reflection of and about Cuba. In order to reach that aim the research appropriates Didi-Huberman's (2015) theoretical basis of the devolution of images and individually analyzes the construction of narratives based on intertextual, contextual, symbolic and metaphorical elements. The research also proposes a comparative analysis between the movies, considering its constants and variables, to better understand the work of co-direction and how it returns the images to Cuba.